Economic Burden, Length of Hospital Stay and Complication of Simultaneous versus Staged Bilateral Hip Arthroplasty: A Hospital Prospective Study - Shen M; Jiang W; Qian P; Cai G; Wu X; Wang J; Ning X; Song L (Dove Medical Press, 2024)
Maoye Shen,1 Wenxue Jiang,1 Ping Qian,1 Gaorui Cai,1 Xiaona Wu,1 Jinghua Wang,2 Xianjia Ning,2 Lixia Song1 1Department of Orthopedics, Shenzhen Third People's Hospital and the Second Hospital Affiliated with the Southern University of Science and Technology, Shenzhen, Guangdong, People's Republic of China; 2Center of Clinical Epidemiology, Shenzhen Third People's Hospital and the Second Hospital Affiliated with the Southern University of Science and Technology, Shenzhen, Guangdong, People's Republic of ChinaCorrespondence: Lixia Song, Department of Orthopedics, Shenzhen Third People's Hospital and the Second Hospital Affiliated with the Southern University of Science and Technology, 29 Bulan Road, Longgang District, Shenzhen, Guangdong Province, 518112, People's Republic of China, Tel + 86-755-61222333, Fax + 86-755-61238928, Email songlixia525529@163.com Xianjia Ning, Center of Clinical Epidemiology, Shenzhen Third People's Hospital and the Second Hospital Affiliated with the Southern University of Science and Technology, 29 Bulan Road, Longgang District, Shenzhen, Guangdong Province, 518112, People's Republic of China, Tel +86-755-61222333, Fax +86-755-61238928, Email xjn0906@163.comBackground: Bilateral hip arthroplasty is a common surgical intervention for patients with bilateral hip disease. The decision between simultaneous versus staged procedures remains debated, primarily due to concerns over cost, postoperative recovery, and complication rates. This study aimed to evaluate the economic burden and clinical outcomes of simultaneous versus staged bilateral hip arthroplasty.Methods: In this single-center, prospective study, patients who underwent bilateral hip replacement at XXX between 2021 and 2022 were included. Participants were divided into groups based on the surgical approach: simultaneous bilateral hip arthroplasty or staged bilateral hip arthroplasty. Data on costs, operation times, hospital stay lengths, and postoperative outcomes were collected and analyzed.Results: A total of 57 patients were studied, with 45 undergoing simultaneous and 12 staged surgeries. The total cost for staged procedures was significantly higher, with a mean difference of 63,967.54 yuan compared to simultaneous procedures. No significant difference was found in prosthesis costs between the groups. Operation times and hospital stays did not significantly differ, with averages closely aligned between the simultaneous (operation time: 3.2 hours, hospital stay: 5 days) and staged groups (operation time: 3.4 hours, hospital stay: 5.2 days). The obesity rate was higher in the simultaneous group (P < 0.05).Conclusion: Simultaneous bilateral hip arthroplasty appears to be an economically favorable option, with comparable perioperative and immediate postoperative outcomes to staged procedures. These insights have significant implications for clinical practice and policy-making, suggesting that simultaneous procedures can be safely implemented for appropriate patients, potentially optimizing healthcare resources.Keywords: Bilateral Hip Arthroplasty, Simultaneous, Staged, Economic Burden, Clinical Outcomes